Comparing two teaching methods based on concept map and lecture on dental students' knowledge and performance of post-exposure prophylaxis to hepatitis B: A quasi-experimental study - Kamran Mirzaei; Mohammadreza Yazdankhahfard; Arghavan Behbahanirad (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Dental students are at high risk of hepatitis B virus (HBV) infection during clinical activities. Therefore, preventive measures are essential after exposure to the HBV. This study aimed to compare the effectiveness of the concept map and the lecture methods on dental students' knowledge and performance regarding hepatitis B post-exposure prophylaxis (PEP) after possible exposure to the HBV. MATERIALS AND METHODS: This quasi-experimental study was conducted on 70 dental students at Shiraz University of Medical Sciences, Iran. Subjects were categorized into two groups, each receiving either the concept map or the traditional lecture methods. After the interventions, dental students' knowledge and performance were measured by a researcher-made questionnaire. RESULTS: The statistical analysis showed significantly higher knowledge and performance in the concept map group compared to the lecture group (P = 0.030 and P = 0.022, respectively). Although both groups' knowledge and performance decreased after the six-month intervention, the second group who received the lecture method showed more decline in knowledge and performance (P = 0.041 and P < 0.001, respectively). CONCLUSION: Both the concept map and lecture methods have proved to be effective ways of improving the knowledge and performance of dental students. However, the present study revealed that the concept method was more effective on dental students' knowledge and performance regarding preventive measures after exposure to HBV. Thus, the concept map method is recommended for informative and educational purposes.